2022
DOI: 10.1038/s41372-022-01472-9
|View full text |Cite
|
Sign up to set email alerts
|

Does videolaryngoscopy improve tracheal intubation first attempt success in the NICUs? A report from the NEAR4NEOS

Abstract: Objective We hypothesized that videolaryngoscope use for tracheal intubations would differ across NICUs, be associated with higher first attempt success and lower adverse events. Study design Data from the National Emergency Airway Registry for Neonates (01/2015 to 12/2017) included intubation with direct laryngoscope or videolaryngoscope. Primary outcome was first attempt success. Secondary outcomes were adverse tracheal intubation associated events and severe desatura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Our study nevertheless provides further evidence that VL is a feasible primary approach to tracheal intubation in critically ill term and preterm infants 14. Intubation is a highly complex procedure.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Our study nevertheless provides further evidence that VL is a feasible primary approach to tracheal intubation in critically ill term and preterm infants 14. Intubation is a highly complex procedure.…”
Section: Discussionmentioning
confidence: 55%
“…It was noticeable, however, that oesophageal intubation with concomitant desaturation did never occur in the VL group. Various studies have reported that oesophageal intubation is the most common and severe adverse TIAE 6 7 14 18. This raises the question which TIAEs are important and whether it is more important to prevent certain adverse TIAEs than others.…”
Section: Discussionmentioning
confidence: 99%
“…A Cochrane systematic review of VL use in neonates reported increased success for the first attempt at TI, but no overall reduction in the number of TI attempts, with modest sample sizes and moderate to very low quality evidence 23. A more recent study from the NEAR4NEOS registry did not find any independent association between VL use and first attempt success 24. As both primary VL use and changing to VL for the second attempt were uncommon, our study was underpowered to make meaningful conclusions about the effects of VL on second attempt success.…”
Section: Discussionmentioning
confidence: 99%
“…According to a retrospective review of prospective collected observational data from the NEAR4KIDS (National Emergency Airway Registry for Children) database, VL use was independently associated with a lower occurrence of TIAEs among PICUs and cardiac ICU patients ( 11 ). In neonatal settings, VL has also been proven to be clinically significant and has been associated with fewer TIAES when compared to DL use ( 6 , 12 , 13 ). In an extensive retrospective review of prospective collected observational data from the National Emergency Airway Registry for Neonates (NEAR4NEOS), Moussa et al found that, although VL use was not independently associated with higher TI first attempt success, it was associated with lower TIAEs ( 13 ).…”
mentioning
confidence: 99%
“…In neonatal settings, VL has also been proven to be clinically significant and has been associated with fewer TIAES when compared to DL use ( 6 , 12 , 13 ). In an extensive retrospective review of prospective collected observational data from the National Emergency Airway Registry for Neonates (NEAR4NEOS), Moussa et al found that, although VL use was not independently associated with higher TI first attempt success, it was associated with lower TIAEs ( 13 ). A systematic review that included three randomized trials that compared VL with DL for neonatal TI by trainees showed that VL increased IT first attempt success rate (moderate evidence) ( 12 ).…”
mentioning
confidence: 99%